Application of a colorimetric DNA-DNA hybridization method for identification of Aeromonas genomic species, isolated from diarrheal stools - Kaznowski, A (Folia microbiologica, 1996)
The colorimetric DNA-DNA hybridization method for the identification of 18 strains of Aeromonas spp. isolated from human stools was used. Bacterial isolates were also examined by phenotypic characteristics. On the basis of biochemical tests 13 strains were included in phenogroup A. caviae and 5 strains in A. sobria. Identification to the species level was obtained by colorimetric hybridization method. DNA-DNA similarity values showed that isolates of A. caviae group belong to hybridization group (HG) 4 whereas isolates of A. sobria belong to HG 8/10. DNA relatedness results obtained by the colorimetric method showed good agreement with values detected by the spectrophotometric method. The background in the colorimetric method is lower than in the spectrophotometric one. Results of this study indicate the usefulness of the colorimetric DNA-DNA hybridization in microplates method for the identification of Aeromonas genomic species, isolated from human diarrheal stools.
Keywords: Gram-Negative Bacterial Infections; kolorimetrie; průjem; DNA bakterií; Infant; feces; Humans; druhová specificita; kojenec; dítě; Child; dospělí; Diarrhea; Aeromonas; difenylamin; lidé; Feces; předškolní dítě; Adult; DNA, Bacterial; Diphenylamine; Species Specificity; Colorimetry; Nucleic Acid Hybridization; gramnegativní bakteriální infekce; hybridizace nukleových kyselin; indikátory a reagencie; Child, Preschool; Indicators and Reagents